PENGARUH LAYANAN PAYLATER DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN PADA GENERASI MILENIAL DI KOTA YOGYAKARTA - Sulastiningsih; Faiz Fernando, Muhammad (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
This research aims to determine the influence of paylater services and financial literacy on the financial behavior of the millennial generation in the city of Yogyakarta. The research method uses quantitative methods by carrying out multiple linear regression between the variables of paylater services and financial literacy on financial behavior. The sample for this research was 399 respondents who were determined by accidental sampling. This research concludes that the variables of paylater services and financial literacy have a significant positive on financial behavior both partially and simultaneously. The R2 value shows 0,411 or 41,1%. This explains that the financial behavior variable can be explained by 41,1% by the paylater service and financial literacy variables. The implication the results of this research for the millennial generation are expected to be able to improve their financial behavior effectively and efficiently and be more responsible in managing finances.